Mathematical modelling of wood drying process - Čiegis, Raimondas; Starikovičius, Vadimas; Volkas, Audrius (Lietuvos matematikos rinkinys, 2000)
This work discusses issues on the design of finite difference schemes for modelling the moisture movement process in the wood. A new finite difference scheme is proposed. The stability and convergence in the maximum norm are proved.